Gamma knife pallidotomy for treatment of Parkinson’s disease: long term results, clinical study - Young, Ronald F.; Li, Francisco; Vermeulen, Sandra; Clayton, Daniel A.; Hesselgesser, Robert D. (Translational Cancer Research, 2014)
Background: Deep brain stimulation (DBS) is now the preferred surgical treatment for advanced Parkinson’s disease (PD). Some patients however are not suitable candidates for an open surgical procedure or may prefer a procedure that does not include the permanent implantation of hardware. For such patients, gamma knife pallidotomy (GKP) may be a suitable alternative. Objective: The goal of this report was to describe the safety and effectiveness of posteroventral pallidotomy (GKP) performed with the Leksell gamma knife (LGK) for the treatment of advanced PD. Methods: Forty patients underwent a total of 51 GKP procedures with LGK between August 1993 and June 2009. Twenty nine patients underwent a unilateral procedure whereas 11 underwent bilateral procedures. Results: There were statistically significant improvements in off-medication unified Parkinson’s disease rating scale (UPDRS) scores for total scores (18.4%), motor scores (18.2%), tremor(72.4%) rigidity (51.2%) and bradykinesia (23.4%) scores and also for on medication dyskinesia scores (70.0%.) Bilateral procedures produced an additional incremental improvement in symptoms. Two patients suffered permanent complications. Conclusions: GKP offers a safe and effective procedure for the treatment of advanced PD. Although probably not as effective as DBS, it is particularly applicable to patients who may not be candidates for DBS.